Risk Analysis of Exposure to Worker Health and Ecosystems at Tin Smelters - Ferly Oktriyedi; Lela Handayani; Dedek Sutinbuk (Indonesian Journal of Global Health Research, 2026)
Indonesia, particularly Bangka Belitung Province, is one of the world's largest tin producers, supporting exports and state revenue. Tin smelting activities (smelters) are a vital part of this metal's production chain. The focus of this research is on production activities, tailings disposal, and chemical refining, which have the potential to cause environmental pollution and health risksThis research is important to provide evidence-based insights into environmental and occupational hazards of tin smelting, enabling targeted mitigation strategies and promoting sustainable industrial practices without compromising public health or environmental integrity. This study used descriptive field observation methods at the tin smelter in June 2025, focusing on the production process, waste management, and occupational safety practices. Data were collected through direct observation and semi-structured interviews with workers, OHS officers, and operational managers. The data were then analyzed qualitatively to identify and describe potential environmental pollution and occupational health risks. This study confirms that tin mining activities, from land clearing to refining, have significant impacts on the environment, public health, and occupational safety. Soil, water, and air pollution from solid and liquid waste and exposure to heavy metals have been proven to threaten the sustainability of the ecosystem and the socio-economic well-being of surrounding communities. Furthermore, mine workers face a high risk of occupational diseases and physical and mental stress. Therefore, a comprehensive mitigation strategy is needed through the implementation of waste management technology, strict OHS standards, environmental quality monitoring, and public health education. These efforts are key to balancing tin industry productivity with sustainable development principles.